2010
DOI: 10.1188/10.onf.774-781
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Easy-to-Read Pamphlets About Self-Care Management of Radiation Side Effects on Patients' Knowledge

Abstract: In addition to written patient information, oncology nurses should use innovative teaching strategies to improve patient understanding and self-care behaviors. A need exists for continued nursing inquiry that will focus on self-care behaviors to manage radiation side effects, particularly for patients with low literacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…However, evidence supporting the effectiveness of only written patient education materials in improving health literacy is not sufficient, since several studies used a nonexperimental design [12] or turned out inconclusive [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence supporting the effectiveness of only written patient education materials in improving health literacy is not sufficient, since several studies used a nonexperimental design [12] or turned out inconclusive [13].…”
Section: Introductionmentioning
confidence: 99%
“…On pictorial cards, the text of instructions was written in a large, bold font (14-point), to accommodate the expected functional health literacy levels and eyesight (Lin, Neafsey, & Strickler, 2009;Wilson, Mood, & Nordstrom, 2010) In addition, questions were provided for all items and presented potential self-medication dilemmas. The answers were selected by choosing cards labeled as O or X.…”
Section: Methodsmentioning
confidence: 99%
“…The intention of the review was twofold: to complement the existing written information by customizing the information that our institution provided and to avoid duplication of what was already available. An important finding from this showed that the reading level for many booklets and documents was at grade 11 level or higher rather than the recommendation of current literacy standards at grade 6 to 8 levels [14,15].…”
Section: Review Of Existing Toolsmentioning
confidence: 99%
“…What became evident in the review of available written tools at our institution was that many of the information tools were not addressing literacy levels. In fact, many tools were found to be at a literacy level of grade 11 or higher rather than a grade 8 level, as recommended when the tool is mediated or assisted by another person [14,15].…”
Section: Patient Education and Literacy Guidelinesmentioning
confidence: 99%